Hydrocarbon Generation Potential of Microbial Carbonate in the Western Qaidam Basin, China: Implication From Thermocompression Experiment - She, Min; Hu, Anping; Lv, Yuzhen; Chen, Wei; Liang, Jintong; Zheng, Lunju (Frontiers in Earth Science, 2022)
The potential of microbial carbonate rocks as hydrocarbon source rocks still remains uncertain. To evaluate the hydrocarbon generation and expulsion capability of microbial carbonate rocks, stromatolite obtained from the Xiaganchaigou formation of the western Qaidam Basin has been used for thermocompression experiments to simulate hydrocarbon generation and expulsion at temperature of 280 to 380°C. The results show that the generation potentials of total oil, residual oil, expelled oil, and hydrocarbon gases for stromatolite are 143.39 to 379.99 mg/g total organic carbon (TOC), 47.08 to 223.92 mg/gTOC, 71.12 to 170.81 mg/gTOC, and 6.60 to 101.74 mg/gTOC, respectively. A three-stage model of hydrocarbon generation and expulsion evolution has been constructed for stromatolite. The results show that the first stage is characterized by relatively slow oil generation with associated hydrocarbon gases, having limited capability of oil expulsion in the temperature range of 280 to 360°C (0.50% ≤ Ro ≤ 0.70%). The second stage is characterized by rapid oil generation with associated hydrocarbon gases, having incremental capability of oil expulsion in the temperature range of 320 to 360°C (0.70% ≤ Ro ≤ 1.15%). The third stage is characterized by hydrocarbon gas generation with associated oil, having efficient oil expulsion capability in the temperature range of 360 to 380°C (1.15% ≤ Ro ≤ 1.45%). The experimental data of argillaceous dolostone, gray mudstone, and marlstone, which were reported with the same hydrocarbon generation experimental method, was compared with the data for stromatolite. Compared with traditional source rocks, the oil generation potential of stromatolite is less than that of argillaceous dolostone and gray mudstone but greater than that that of marlstone in the same amount of organic carbon. Especially, the hydrocarbon gas generation potential of stromatolite is approximately double than that of traditional source rocks. Therefore, the experiments indicate that the microbial carbonate rocks in the western Qaidam Basin could be effective source rocks.